Teacher Perception of ICT Integration in Teaching and Learning at Elementary Level - Asifa Ishaq,; Muqaddas Rani,; Fazal Abbas,; Dr. Khalid Mahmood Arif,; Rizwana Bashir Zia, (Al-Qanṭara, 2023)
The rapid spread of information and communication technology (ICT) has transformed learners into digital learners, requires teachers to integrate technology into their educational approaches, and effective integration depends on teacher attitudes, technical knowledge and skills play an important role. In this context, the quantitative survey demonstrates, teachers' perceptions of technology integration in teaching and learning practices at the elementary school level in Tehsil Kamalia District Toba Tek Singh. A random sampling technique was used in this study and data were collected using a self-designed questionnaire. Data from this quantitative study were analyzed using SPSS software for both descriptive and inferential statistics. This result shows that ICT integration is highly effective for both teachers and students. The results show that use of ICT tools is one of the key factors for successful technology-enabled teaching and learning and as a result, teachers are positive about technology integration in their teaching and learning practices. It was shown that they have a strong awareness of technology-integrated in education that can effectively improve teaching practices, make the learning process engaging and interactive, help and keep learners engaged. Slow internet speeds, load shedding, lack of infrastructure, and online teaching experience and training were identified as the main obstacles preventing a teacher from effectively integrating ICT into teaching practice. Future research should consider other aspects of ICT integration, particularly from a management perspective in terms of strategic planning and policy making.